Brassinosteroids Influence Arabidopsis Hypocotyl Graviresponses through Changes in Mannans and Cellulose. (11th February 2021) - Somssich, Marc; Vandenbussche, Filip; Ivakov, Alexander; Funke, Norma; Ruprecht, Colin; Vissenberg, Kris; VanDer Straeten, Dominique; Persson, Staffan; Suslov, Dmitry
Abstract: The force of gravity is a constant environmental factor. Plant shoots respond to gravity through negative gravitropism and gravity resistance. These responses are essential for plants to direct the growth of aerial organs away from the soil surface after germination and to keep an upright posture above ground. We took advantage of the effect of brassinosteroids (BRs) on the two types of graviresponses in Arabidopsis thaliana hypocotyls to disentangle functions of cell wall polymers during etiolated shoot growth. The ability of etiolated Arabidopsis seedlings to grow upward was suppressed in the presence of 24-epibrassinolide (EBL) but enhanced in the presence of brassinazole (BRZ), an inhibitor of BR biosynthesis. These effects were accompanied by changes in cell wall mechanics and composition. Cell wall biochemical analyses, confocal microscopy of the cellulose-specific pontamine S4B dye and cellular growth analyses revealed that the EBL and BRZ treatments correlated with changes in cellulose fibre organization, cell expansion at the hypocotyl base and mannan content. Indeed, a longitudinal reorientation of cellulose fibres and growth inhibition at the base of hypocotyls supported their upright posture whereas the presence of mannans reduced gravitropic bending. The negative effect of mannans on gravitropism is a new function for this class of hemicelluloses. We also found that EBL interferes with upright growth of hypocotyls through their uneven thickening at the base.